Developments in numerical and experimental methods applied to tribology : proceedings of the 10th Leeds-Lyon Symposium on Tribology held at the Institut National des Sciences Appliquees, Lyon, France, 6th-9th September 1983 - Dowson, D. (Butterworths for the Institute of Tribology, Leeds University and the Institut national des Sciences appliquees Lyon, 1984)
Developments in Numerical and Experimental Methods Applied to Tribology contains the proceedings of the 10th Leeds-Lyon Symposium on Tribology held at the Institut National des Sciences Appliquies in Lyon, France, on September 6-9, 1983. The papers explore developments in numerical and experimental methods used in tribology and cover topics ranging from ferrography and rheology to bearings and bearing dynamics, hydrodynamics, contact phenomena, and plasticity.